+0  
 
+9
511
1
avatar+730 

Find t if the expansion of the product of x^3 - 4x^2 + 2x - 5 and x^2 + tx - 7 has no x^2 term.

MIRB16  Aug 5, 2017
 #1
avatar+26752 
+1

x2 terms come from:  (-4)*(-7) + 2t + (-5)*1 → 28 + 2t -5 → 23 + 2t

 

For this to be zero we must have 23 + 2t = 0. or t = -23/2 → -11.5

.

Alan  Aug 5, 2017

9 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.